Réponses

2014-03-06T16:31:19+01:00
Bonjour

A = 2/7 -15/7 : 5/4
A = 2/7 - 15/7 x 4/5
A = 2/7 - 60/35
A = 10/35 - 60/35 = -50/35
A = -10/7

B = 60 x 10² sur 80 x 10^-1
B = 0.75 x 10^3
B = 750 et 7.5 x 10²

C = √75 +4√27 -5√48
C = 5√3 + 12√3 - 20√3
C = -3√3

D = (2+4√5)(2-4√5)
D = 4 - 80 = -76

E = 9x² + 12x +4 - (3x² +21x +2x +14)
E = 9x² +12x +4 -3x² -21x -2x -14
E = 6x² -11x -10

E = (3x+2)(3x+2 - x -7)
E = (3x+2)(2x -5)

pour x = 1/2
E = (3/2+2)(2/2 -5)
E = (3/2 + 4/2)(2/2 - 10/2)
E = 7/2 x -8/2 = -56/4
E = -14

(3x+2) = 0
3x = -2
x = -2/3

2x-5 = 0
2x = 5
x = 5/2